The reference range of serum, plasma and erythrocyte magnesium (Faculty of Medicine Universitas Indonesia, 2006)
The interest in the clinical importance of serum magnesium level has just recently begun with the analysis and findings of abnormal magnesium level in cardiovascular, metabolic and neuromuscular disorder. Although the serum level does not reflect the body magnesium level, but currently, only serum magnesium determination is widely used. Erythrocyte magnesium is considered more sensitive than serum magnesium as it reflects intracellular magnesium status. According to NCCLS (National Committee for Clinical Laboratory Standards) every laboratory is recommended to have its own reference range for the tests it performs, including magnesium determination. The reference range obtained is appropriate for the population and affected by the method and technique. This study aimed to find the reference range of serum and plasma magnesium and also intracellular magnesium i.e. erythrocyte magnesium by direct method, and compare the results of serum and plasma magnesium. Blood was taken from 114-blood donor from Unit Transfusi Darah Daerah (UTDD) Budhyarto Palang Merah Indonesia (PMI) DKI Jakarta, consisted of 57 male and 57 female, aged 17 â 65 years, clinically healthy according to PMI donor criteria. Blood was taken from blood set, collected into 4 ml vacuum tube without anticoagulant for serum magnesium determination and 3 ml vacuum tube with lithium heparin for determination of erythrocyte and plasma magnesium Determination of magnesium level was performed with clinical chemistry auto analyzer Hitachi 912 by Xylidil Blue method colorimetrically. This study showed no significant difference between serum and heparinized plasma extra cellular magnesium. The reference range for serum or plasma magnesium was 1.30 â 2.00 mEq/L and for erythrocyte magnesium was 4.46 - 7.10 mEq/L. (Med J Indones 2006; 15:229-35)Keywords: Reference range, extracellular magnesium, intracellular magnesium